Asian-Australian monsoon evolution over the last millennium linked to ENSO in composite stalagmite δ18O records. (1st April 2022) - Zhang, Jian; Liang, Ming-Qiang; Li, Ting-Yong; Chen, Chao-Jun; Li, Jun-Yun
Abstract: The Asian-Australian monsoon (AAM) system distinctly influences global climate. However, the linkage between ENSO (El Niño–Southern Oscillation) and AAM is still poorly understood over the last millennium. Here, we combined stalagmite δ 18 O (δ 18 Os ) records with exceptionally high-resolution and high-precision chronologies to demonstrate a tight remote coupling between AAM and tropical ocean hydrology on the multi-year, decadal, and centennial timescales. Our results reveal that (1) There is a significant negative correlation between the multi-year weighted average precipitation δ 18 O (δ 18 Oaw ) from the AAM and Southern Oscillation Index (SOI), providing a modern analogous coupling for linking stalagmite δ 18 O (δ 18 Os ) and ENSO over the past 100 years. (2) Over the last millennium, the integrated δ 18 Os record exhibit positive excursions during the Little Ice Age (LIA), marked by a tendency for more El Niño-like state conditions in the tropical Pacific, which is consistent in SST-gradient ENSO reconstruction but different to precipitation reconstruction. (3) Wavelet and power spectrum analysis for the integrated δ 18 Os record in the AAM region show that there is a significant multi-year periodicity (2.2, 2.8, 3.5, 4.6 yr), conceding with the ENSO cycle (2–7 yr), whereas, some multi-decadal and centennial cycles (10.1, 17, 28.6, 52.7, 143 yr) are significant too. We provide evidence from instrumental and paleocliamte datasets (GNIP and NOAA) and propose a possible "circulation effect" mechanism responsible for variations of δ 18 Os in the East Asian Monsoon (EAM) and Australian Monsoon (AM) region over the last millennium. Highlights: A strong link exists between the modern precipitation δ 18 O and SOI in the AAM. Changes in moisture sources under different ENSO phases modulated the variation of stalagmite δ 18 Os in the EAM and AM. The evolution of ENSO over the last millennium is reconstructed based on composite stalagmite δ 18 Os records.